Leksikon Mistis dalam Kanal YouTube Kisah Tanah Jawa 2023/2024: Kajian Antropolinguistik - Erin Winda Maharani; Rawinda Fitrotul Mualafina; Latif Anshori Kurniawan (Departement of Mathematics Education, 2024)
This research aims to analyze the use and meaning of the mystical lexicon that appears on the YouTube channel Kisah Tanah Jawa (Tanah Jawa Stories) during 2023 to 2024. This channel is known for its content that raises mystical themes, including beliefs, rituals, and spiritual practices in Javanese culture. This research method uses descriptive-qualitative with data in the form of a mystical lexicon and data sources in the form of video recordings. The technique in this research uses the agih and matching method with anthropolinguistic studies. The results of this research found 22 mystical lexicon data in the form of basic words, 8 mystical lexicon data in the form of affixes, 5 mystical lexicon data in the form of phrases, 7 mystical lexicon data in the form of loan words, and 3 data in the form of foreign language usage lexicons. The use of the term mystical lexicon makes an important contribution to understanding the relationship between language, culture, and digital media, as well as how mystical lexicons are maintained and developed in contemporary contexts. It is hoped that these findings can broaden insight into the role of language in the preservation and transformation of culture in the digital era.